The Politics of Imagination Benjamin, Kracauer, Kluge - Forrest, Tara (Kultur- und Medientheorie, 2007)
This book explores Walter Benjamin, Siegfried Kracauer and Alexander Kluge's analyses of the role that a rejuvenation in the capacity for imagination can play in encouraging us to reconceive the possibilities of the past, the present, and the future outside of the parameters of the status quo. The concept of imagination to which the title of the book refers is not a strictly defined, stable concept, but rather a term which is employed to refer to a capacity that facilitates both an active, creative relationship to one's environment, and a process of mediation between the outside world and one's own experiences and memories. Through a detailed analysis of their engagements with subjects that span a broad range of historical and thematic contexts (including topics as diverse as literature, children's play, film, photography, history, and television) the book charts the extent to which the concept of imagination plays a central role in Benjamin, Kracauer, and Kluge's explorations of a mode of perception and experience which could serve as a catalyst for the creation and sustenance of a desire for a different kind of future.